The crucial and contested concept of the endonym/exonym divide - Jordan, Peter (Instytut Języka Polskiego Polskiej Akademii Nauk, 2021)
Paul Woodman has called it the “great toponymic divide”, but the endonym/exonym distinction is not a concept confined solely to toponymy, it can be transferred to all name categories, where the name used by insiders may differ from the name used by outsiders, e.g., to ethnonyms, anthro ponyms, names of institutions, where we frequently meet, for instance nicknames and derogative designa- tions used by outsiders. But there is no doubt that this divide has its focus on toponymy, since it corresponds there to two basic human attitudes: (1) to the distinction between ‛mine’ and ‛yours’, ‛ours’ and ‛theirs’, and (2) to territoriality, the desire to own a place, which appears at all levels of the construction of human community  — from the level of the family up to that of nations. Thus, it has always a political, social, and juridical meaning and is frequently a reason for dispute and conflict. However, even after long and intensive discussions, e.g., in the UNGEGN Working Group of Exonyms, to date we can still see rather divergent approaches to this divide. There is the linguistic approach regarding the endonym and the exonym rather as poles of a continuum, with various intermediary stages. Alternatively, there is the cultural-geographical approach that accepts no other criteria than the spatial relation between the name-using community and the geographical feature denoted by the name. The article elaborates on these items, mainly on the basis of the discussions and publications of the UNGEGN Working Group on Exonyms since 2002.
265 pages ; 23 cm.
Keywords: exonyms; toponymy; terminology; UNGEGN; cultural geography